Cultural Diplomacy The Icelandic Way : the current state of Iceland’s cultural diplomacy practices - Bergþóra Laxdal 1973- (2017)
This 30 ECT credit MA thesis is a case study that discusses the role of the Government of Iceland and the creative centers in Iceland when publicly funding cultural projects that take place internationally. The objective is to examine the current state of how the Government of Iceland conducts its cultural diplomacy practices. In examining the Government practices on this topic, the following three questions are pursued; is there an informal cultural diplomacy policy in place; what principles drive that policy and what strategic approach is in place to fulfill the policy? The participants were selected due to their expertise in the cultural affairs of Iceland, and were divided into two groups. The first group, the Expert Committee on Art and Culture Expert Committee on Art and Culture headed by Promote Iceland, was selected to identify the Government agencies from which the creative centers receive their public funding and to gain insight into how projects that receive public funding are selected to represent Iceland abroad. This group delivered their answers in a written open ended questionnaire. The second group, Government cultural representatives with responsibilities in distributing public funding, was selected to get an overview of how the distribution of funds takes place and delivered their answers through an interview. The results were analyzed according to theories about policy and policy streams and strategy processes. The results support the view of an informal cultural policy being in place. The creative centers are responsible for deciding what cultural projects receive public funding with the Government trusting in the center’s professional abilities, and handling the financial transactions through the creative centers. Thesis advisor was Dr. Gregory Payne, Associate Professor and Chair, Department of Communication Studies at Emerson College in Boston, MA. Keywords: Cultural diplomacy; Cultural Management; Cultural Policy; Culture; Iceland.